Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1103/physrevlett.121.078002
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder Structural Transitions in Mazes Built by Evaporating Drops

Abstract: We show that the evaporation of surfactant solutions confined in quasi-two-dimensional porous media creates micron-sized labyrinthine patterns composing the walls of a centimeter-sized maze. These walls are made of solid deposits formed during drying via a sequence of individual Haines jumps occurring at the pore scale. We rationalize this process driven by simple iterative rules with a cellular automaton that acts as a maze generator. This model well describes the formation dynamics and final structure of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…12a-c. Similar bridge configurations are observed in experiments from studies (Hamon et al 2012;Bizien et al 2014;Panizza et al 2016) as shown in Fig. 12d-f.…”
Section: Effects Of Initial Particle Concentration In Large Systemssupporting
confidence: 85%
“…12a-c. Similar bridge configurations are observed in experiments from studies (Hamon et al 2012;Bizien et al 2014;Panizza et al 2016) as shown in Fig. 12d-f.…”
Section: Effects Of Initial Particle Concentration In Large Systemssupporting
confidence: 85%
“…A step further towards more realistic biomimetic chips would also consist in replacing the PDMS by more hygrophilic materials such as hydrogels or cellulose-based porous materials. Recent studies showed for both wood (Penvern et al 2020) and cellulose-based fabrics (Ma et al 2022) that the higher water solubility of these materials leads to dynamics characterised by a most significant role played by bound water.…”
Section: Discussionmentioning
confidence: 99%
“…Once the meniscus reaches its maximal possible curvature compatible with the geometrical constraints and the contact angles of water on PDMS and glass, the situation becomes unstable, because the Laplace pressure can no longer equilibrate the elastic deformation of the channel, and the meniscus advances rapidly until the channel is fully relaxed. The onset of the jump is therefore an occurrence of a capillary threshold, as encountered in the drainage of Newtonian fluids in porous media (Wilkinson & Willemsen 1983; Lenormand & Zarcone 1985;Måløy, Feder & Jøssang 1985;Méheust et al 2002), in the flow of foams in porous media (Géraud et al 2016), or in the pervaporation dynamics in an array of micropillars (Panizza et al 2018). Hence the maximal deformation of the channel is correlated, through Laplace pressure, to the maximal curvature of the meniscus.…”
Section: Confocal Imaging Of the Deformation Of The Channel During Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we used a previously developed approach in which we let dry an aqueous suspension of QRs in between a flat substrate, either a silicon wafer or a glass coverslip, and a PDMS stamp on which round pillars, 35 μm high and 100 μm in radius, are regularly spaced by 75 μm on a square lattice (Figure 2(a)) [36,43]. More precisely, sample QR Pattern S2A).…”
Section: Qr Supracrystals Synthesis and Morphological Characterizationmentioning
confidence: 99%